Serotonin production of the developing gastrointestinal tract of human embryos in 6th gestation week - Nadya Penkova; Pepa Atanasova; Radoslav Penkov; Petar Hrischev; Lyudmil Peychev; Zhivko Peychev (Pensoft Publishers, 2023)
Background: Local regulation of gastrointestinal tract digestion is performed by a large number of hormones produced by the mucosal enteroendocrine cells. Some of the earliest differentiating cells in the gastrointestinal tract are enteroendocrine cells. Serotonin-producing cells - EC cells are found mostly in the stomach and duodenum. Aim: The aim of our study is to establish the presence and to make morphological and morphofunctional characteristic of ЕС cells in the developing gastrointestinal tract of a human. Materials and methods: Our study was performed with biopsy specimen from human stomach and duodenum and fragments of gastrointestinal tract of human embryos 6th gestation week, studied by immunohistochemical, electron microscopy and morphometric methods. Results: EC cells have already been differentiated in the 6th gestation week. Embryonic EC cells had identical characteristics with those of adults. They were in two morphofunctional conditions: stage of increased synthesis and stage of relative secretory rest. Conclusion: In the early embryonic period - 6th gestation week EC cells have already been differentiated. The occurrence of EC cells with hormonal production prior to the definitive differentiation of tissues presupposes participation of serotonin in the digestive tube histogenetic processes.